Poverty, Environment and Development Nexus: A Review from Existing Literature - Bhattarai, Lekha Nath (Himalayan Journal of Sociology and Anthropology, 2008)
No abstract available. Himalayan Journal of Sociology & Anthropology Vol.1 2004, p.138-160